2008
DOI: 10.1111/j.1467-789x.2007.00426.x
|View full text |Cite
|
Sign up to set email alerts
|

Disinhibition: its effects on appetite and weight regulation

Abstract: Over the past 30 years, the understanding of eating behaviour has been dominated by the concept of dietary restraint. However, the development of the Three Factor Eating Questionnaire (TFEQ), introduced two other factors; Disinhibition and Hunger, which have not received as much recognition in the literature. The objective of this review is to explore the relationship of the Disinhibition factor to weight regulation, food choice and eating disorders, and to consider its etiology. The review indicates that Disi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
255
5
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(289 citation statements)
references
References 108 publications
21
255
5
8
Order By: Relevance
“…In a randomized weightloss programme Keränen et al reported that cognitive restraint was associated with lower energy and fat intakes, whereas carbohydrates and fibre intakes were higher (42) . In a review from Bryant et al disinhibition was reported to be associated with a less healthy food choice (15) . In contrast, the analysis of the Québec Family Study showed that dietary macronutrient content was not consistently related to eating behaviour traits in adolescents (22) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a randomized weightloss programme Keränen et al reported that cognitive restraint was associated with lower energy and fat intakes, whereas carbohydrates and fibre intakes were higher (42) . In a review from Bryant et al disinhibition was reported to be associated with a less healthy food choice (15) . In contrast, the analysis of the Québec Family Study showed that dietary macronutrient content was not consistently related to eating behaviour traits in adolescents (22) .…”
Section: Discussionmentioning
confidence: 99%
“…In various populations previous studies suggest that eating behaviour traits correlate with body weight (13)(14)(15) . Most studies suggest that high levels of restraint eating but also of disinhibition are positively associated with a higher BMI and weight gain over time.…”
mentioning
confidence: 99%
“…9 Examples of disinhibition include eating in response to negative affect, overeating when others are eating, not being able to resist eating, and overeating in response to the palatability of food. In particular, individuals characterized by a high disinhibition eating behavior score have a higher liking for sweet and high-fat foods.…”
Section: Sleep Duration Groups Change In Wc (Cm)mentioning
confidence: 99%
“…As its name indicates, the questionnaire was devised to 29 measure three aspects of human eating, defined by the authors as restraint 30 (TFEQ-R), disinhibition (TFEQ-D) and hunger (TFEQ-H). Originally, these scales 31 were designed to measure long-term attitudes to eating and consequently scores 32 are often considered as long-term or trait measures (Barkeling, King, Näslund, & 33 Blundell, 2007;Bryant, King, & Blundell, 2008;Finlayson, Cecil, Higgs, Hill, & 34 Hetherington, 2012;Gallant, et al, 2013;Gallant, et al, 2010;Lattimore, Fisher, & 35 Malinowski, 2011). However, this implies that answers to items on the TFEQ 36 reflect long-term influences on each individual's eating and are thus insensitive 37 to the acute appetitive state of the participant.…”
Section: Introduction 24 25mentioning
confidence: 99%
“…The TFEQ-D scale has been described variously as a measure of trait 53 disinhibition (Lattimore, et al, 2011;Neale, Mazzeo, & Bulik, 2003), uncontrolled 54 eating (Keskitalo, et al, 2008;Yeomans, Leitch, & Mobini, 2008) or opportunistic 55 eating (Bryant, et al, 2008;Finlayson, et al, 2012), reflecting a recognition that 56 the name disinhibition is confounded with the disinhibition effect arising from 57 the breakdown of dietary restraint. Indeed, a shortened version of the TFEQ 58 combined items from the original TFEQ-D and TFEQ-H scales into measure of 59 uncontrolled and emotional eating (Karlsson, Persson, Sjostrom, & Sullivan, 60 2000).…”
mentioning
confidence: 99%